Synthesis of Three-Dimensional Covalent Organic Frameworks and Applications in Electrocatalysis - Wang, Xiaoxiao; Yin, Kaiyao; Ma, Qiao (International Journal of Materials Science and Technology Studies, 2026)
Covalent organic frameworks (COFs) are a novel class of materials held together by covalent bonds, sparking a research boom in recent decades. However, due to the challenges involved in research, studies on COFs have often focused on two-dimensional covalent organic frameworks (2D COFs), while research on three-dimensional covalent organic frameworks (3D COFs) which are more difficult to prepare remains in its initial stages. 3D COFs offer a novel material platform for photocatalysis due to their tunable frameworks, adjustable pore channels, and abundant organic functionalization sites. This paper first focuses on the synthesis methods of 3D COFs. Subsequently, characterization techniques for 3D COFs are introduced. Then, the applications of 3D COFs in electrocatalysis are highlighted. Finally, the challenges and prospects for the future development of 3D COFs are discussed.